2013
DOI: 10.1002/oby.20204
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic sex steroids contribute to metabolic risk beyond intra‐abdominal fat in overweight/obese black and white women

Abstract: Objective: To determine the independent contribution of androgenic sex hormones beyond visceral adipose tissue (VAT) on metabolic risk. Design and Methods: A cross-sectional evaluation of 66 (36 white and 30 black) premenopausal overweight/obese women using multiple regression analyses to determine the independent effects of sex hormone-binding globulin (SHBG), total testosterone (TT), and free testosterone using the free androgen index (FAI) on metabolic variables above VAT. Results: SHBG contributed to the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…However, the sensitivity analyses between women and men revealed the mediation effect values are quite different, that is the difference TyG index mediation effect on BMI-hypertension (25.24% in women and 57.35% in men). It has been reported that androgenic sex hormones contributed to the variance in insulin resistance [31] and estrogen deficiency appears to be associated with an increased risk for the development of most of the clinical features comprising hypertension [32]. This mechanism can be explained precisely by the difference between the mediation effect between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity analyses between women and men revealed the mediation effect values are quite different, that is the difference TyG index mediation effect on BMI-hypertension (25.24% in women and 57.35% in men). It has been reported that androgenic sex hormones contributed to the variance in insulin resistance [31] and estrogen deficiency appears to be associated with an increased risk for the development of most of the clinical features comprising hypertension [32]. This mechanism can be explained precisely by the difference between the mediation effect between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…However, the testosterone levels were similar among premenopausal and postmenopausal women. This suggested that fat redistribution may be affected by a marked decreased in estrogen levels but not by increased testosterone level [23]. Estrogen and androgen receptors are expressed in visceral and subcutaneous fat cells.…”
Section: Menopause-associated Changes In Fat Mass and Fatty Acid Metabolismmentioning
confidence: 99%
“…A race interaction was also demonstrated, indicating a strong positive relationship between glucose and FAI in White women while almost no relationship was shown in Black women. Thus, Perry [72] reported a direct effect of androgenic sex steroids on several metabolic variables associated with CVD and diabetes risk that was independent of VAT. She also showed that androgenic sex steroids may not be a good indicator of insulin/glucose status in Black women.…”
Section: Race Differences In Androgenic Sex Steroids and Its Relationmentioning
confidence: 96%
“…Perry et al [72] examined this relationship further in overweight/obese Black and White premenopausal women. She observed that both VAT and androgenic sex steroids were significantly associated with the metabolic risk profile.…”
Section: Race Differences In Androgenic Sex Steroids and Its Relationmentioning
confidence: 97%